Recent Advances in the Structural Design of Photosensitive Agent Formulations Using "Soft" Colloidal Nanocarriers - Agata Pucek; Beata Tokarek; Ewelina Waglewska; Urszula Bazylińska (MDPI AG, 2020)
The growing demand for effective delivery of photosensitive active compounds has resulted in the development of colloid chemistry and nanotechnology. Recently, many kinds of novel formulations with outstanding pharmaceutical potential have been investigated with an expansion in the design of a wide variety of "soft" nanostructures such as simple or multiple (double) nanoemulsions and lipid formulations. The latter can then be distinguished into vesicular, including liposomes and "smart" vesicles such as transferosomes, niosomes and ethosomes, and non-vesicular nanosystems with solid lipid nanoparticles and nanostructured lipid carriers. Encapsulation of photosensitive agents such as drugs, dyes, photosensitizers or antioxidants can be specifically formulated by the self-assembly of phospholipids or other amphiphilic compounds. They are intended to match unique pharmaceutic and cosmetic requirements and to improve their delivery to the target site via the most common, i.e., transdermal, intravenous or oral administration routes. Numerous surface modifications and functionalization of the nanostructures allow increasing their effectiveness and, consequently, may contribute to the treatment of many diseases, primarily cancer. An increasing article number is evidencing significant advances in applications of the different classes of the photosensitive agents incorporated in the "soft" colloidal nanocarriers that deserved to be highlighted in the present review.